The effectiveness of CCTV implementation by municipal council for public safety / Mohd Noor Adam Mohd Nordin - Mohd Nordin, Mohd Noor Adam (Faculty of Architecture, Planning and Surveying, 2008)
Closed Circuit Television Cameras (CCTV) have become an important crime prevention and security measure world-wide. In Malaysia, in the set up of the Safe City Program, CCTV is one of the integral parts of it. With the target of protecting the safety of the public, it is essential that a study being done to ensure the effectiveness CCTV system implementation in terms of enhancing safety with a relevant operational cost. In this dissertation, the aim and objectives are obviously to investigate the effectiveness of CCTV implementing in enhancing the safety of the public, to understand deeply on CCTV as a safety appliances, and at last to develop a conclusion on whether CCTV is the right option in overcoming safety problem and its effect in interrupting with the public privacy. The study and research is limited only on three major city area with municipal council that are Shah Alam (under Majlis Bandaraya Shah Alam municipal), Kuala Lumpur (under Dewan Bandaraya Kuala Lumpur municipal) and Subang Jaya (under Majlis Perbandaran Subang Jaya municipal). The research and data documented in this dissertation came from series of interview sessions with the particulars municipal’s expert in CCTV system, residence respond in the questionnaire and field trip to all three of the case studies area. From the entire information achieved, a conclusion on CCTV effectiveness can be resolved. Effectiveness here based on the opinion and perspective view of professional and expert of CCTV together with the respondent that live in the area where their municipals implemented CCTV. The outcome shows that majority of the public and all of the experts agree on the effectiveness of CCTV implementation for public safety but before that a very detail and particular research must be conducted, so that the CCTV system picked is the best in terms of its location, condition, coverage, quantity, safety provided, maintenance, no privacy intrusion and its overall performance.